Imaging Dose-dependent Pharmacokinetics of an RGD-Fluorescent Dye Conjugate Targeted to αβ Receptor Expressed in Kaposi's Sarcoma - Sunkuk Kwon; Shi Ke; Jessica P. Houston; Wei Wang; Qingping Wu; Chun Li; Eva M. Sevick-Muraca (Molecular Imaging)
Dynamic fluorescence images were obtained from xenografts bearing a subcutaneous human Kaposi's sarcoma (KS1767) immediately following the intravenous injection of an integrin-receptor targeting Cy5.5-c(KRGDf) at a dose ranging from 0.75 to 6 nmol/mouse. The fluorescence images were acquired using an intensified charge-coupled device system and were analyzed with a three-compartment pharmacokinetic (PK) model to determine uptake parameters in the tumor and normal tissue regions of interest as a function of administered dose. Our results show that the uptake of Cy5.5-c(KRGDf) in tumor regions were: (i) significantly greater than the contralateral normal tissue regions; (ii) linearly increased with dose of Cy5.5-c(KRGDf) up to 1.5 nmol/mouse; and (iii) blocked by preinjection of c(KRGDf). Above doses of 1.5 nmol/mouse, the uptake no longer increased with dose, suggesting integrin receptor saturation. In normal tissues, the PK uptake parameters were not influenced by Cy5.5-c(KRGDf) dose nor by the preadministration of c(KRGDf).